The effect of Ringer’s acetate versus Ringer’s lactate on aminotransferase changes in dengue hemorrhagic fever - Mulya Rahma Karyanti; Hindra Irawan Satari; Damayanti Rusli Sjarif (Paediatrica Indonesiana, 2005)
Background Dengue hemorrhagic fever (DHF) infection causeshepatocelullar impairment. In management of DHF, World HealthOrganization (WHO) recommends the crystalloids Ringer’s acetate(RA) or Ringer’s lactate (RL), which are similar in composition toplasma. Acetate in RA is not metabolized in the liver, hence notburdening the liver, whereas lactate in RL is metabolized mostly inthe liver, thus placing a burden on the liver.Objective To compare aminotransferase changes as markers ofhepatocellular impairment subsequent to the use of RA and RL inthe management of DHF with and without shock.Methods This study was a double-blind randomized controlledtrial on DHF patients aged 1-18 years in Cipto MangunkusumoHospital who had not received prior treatment with crystalloids orcolloids. Subjects were randomly assigned to receive either RA orRL intravenously. Aminotransferase levels were examined on thefirst, second and third weeks from the onset of fever.Results Ninety-two patients who fulfilled inclusion criteria wereenrolled in this study, consisting of those without and with shock.Mean transaminase levels of patients without shock in the RA andRL groups did not differ significantly. Mean transaminase levels ofpatients with shock in the RA group were lower than those in theRL group, but this difference was not significant statistically. Meanalteration of transaminase levels in patients with and without shockwere not significantly different.Conclusion In DHF without shock, there is no significant differ-ence between aminotransferase level changes of patients receiv-ing RA and RL solutions. In DHF with shock, aminotransferaselevels of patients receiving RA tend to be lower than those receiv-ing RL, but this difference is insignificant